Water Buffalo and Sugar Cane, Trinidad, W.I. - (:unkn) unknown (Y. De Lima and Co., Ltd., Trinidad, 2009)
The picture shows a water buffalo pulling a cart full of sugarcane.
Colour; Coloured; Style: Landscape; Other: Unbordered, Undivided
Keywords: Trinidad and Tobago; Postcards; Sugarcane industry; Water buffalo; Agriculture